CONTENT-PROCESS APPROACH IN PROJECTING PROFESSIONALISM OF A MODERN TEACHER - L.V. Kondrashova (Academy of Cognitive and Natural Sciences, 2010)
The article reveals the essence, the main haracteristics of content-proceural approach in learning and its possibilities in the professional formation of futre teachers in university education.